ETHNO BIOLOGICAL STUDIES ON HONEY AMONG THE KANIKKARS OF AGASTHIYAMALAI BIOSPHERE, PECHIPARAI FOREST RANGE OF WESTERN GHATS - ARIHARAN V N,; NAGENDRA PRASAD P, (International Journal of Pharma and Bio Sciences, 2014)
Honey is an energy rich medical product produced by honey bees. There are different species of Honey Bees. Honey Bees include Stinged Bee is commonly known as Indian Honey Bee, Apis cerana sub species indica and stingless Honey Bee Trigona irridipennis. The stingless bees are very small, 1-2mm in length and resident species which nest among boulders, old walls, dead trees and tree cavities. They are widely distributed in tropical and temperate regions of the world expect African countries. Among the animal products used by the Kanikkars, honey is one among them. It is a dietary supplement and a medicine too. Kani’s are masters in honey hunting. They collect the honey with the help of bow and arrow from the tall trees or steep mountains. While going for hunting they perform special poojas by keeping the bow and arrow in front of the Goddess and also get the blessings from the Pilathi; who is the head man of the aboriginals. The information of various uses of honey among the tribal people is collected and presented in the present study.